Large-scale load capacity tests on a geosynthetic encased column - Alkhorshid, Nima R.; Araujo, Gregório L.S.; Palmeira, Ennio M.; Zornberg, Jorge G. (Geotextiles and geomembranes, 2019)
Stone columns have been used to minimize the settlement of embankments on soft soils but their use in very soft soils can become challenging, partly because of the low confinement provided by the surrounding soil. Geosynthetic encased columns (GECs) have been successfully used to enhance to reduce settlements of embankments on soft soils. This paper describes an investigation on the performance of encased columns constructed on a very soft soil using different types of encasement (three woven geotextiles with different values of tensile stiffness) and different column fill materials (sand, gravel and recycled construction and demolition waste, RCDW). The results of load capacity tests conducted on large-scale models constructed to simulate the different types of GECs indicate that the displacement method adopted during column installation can lead to an enhanced shear strength in the smear zone that develops within the very soft soil. In addition, breakage of the column fill material was found to affect the load-settlement response of gravel and RCDW columns. Furthermore, the excess pore water pressure generated in the surrounding soil during installation, was found to remain limited to radial distances smaller than three times the GEC diameter.